From Bench to Bedside: Evaluation of AHCC Supplementation to Modulate the Host Immunity to Clear High-Risk Human Papillomavirus Infections - Smith, Judith A.; Mathew, Lata; Gaikwad, Anjali; Rech, Barbara; Burney, Maryam N.; Faro, Jonathan P.; Lucci, Joseph A.; Bai, Yu; Olsen, Randall J.; Byrd, Teresa T. (Frontiers in Oncology, 2019)
Objective: There is currently no effective medicine or supplement for eradication of HPV infections. We have taken a systematic approach evaluating the potential use of AHCC supplementation to support eradication HPV infections. The primary objective of this research was to evaluate AHCC supplementation to modulation of the host immune system to eradicate high-risk human papillomavirus (HR-HPV) infections from bench to bedside. Methods: Cervical cancer cells, SiHa(HPV16/18+) and C-33A(HPV-), were treated in vitro with AHCC 0.42 mg/mL daily x7 days then observed x7 days with daily sample collection. A confirmatory study in cervical cancer mouse models, SiHa(HPV+) and C-33A(HPV-), was conducted: AHCC 50 mg/kg/d (N=10), vehicle (N=10), or no supplementation (N =10) x90 days followed by 30 days of observation. Tumors were measured 3x/week and blood samples collected bi-weekly to evaluate interferon (IFN) alpha(α), beta(β), and gamma and immunoglobulin G1(IgG1) by immunoassays. Tumors were evaluated for HR-HPV expression by PCR. Two 10 patient pilot studies were conducted in women with confirmed persistent HR-HPV+ infections. The 1st study evaluated AHCC 3g from 5 weeks up to 6 months and 2nd study evaluated AHCC 1g<8 months. HR-HPVDNA status and the immune panel were monitored at each visit. Results: HR-HPV eradication was observed in vitro and confirmed in the animal studies as a durable response. Four of six (66.7%) patients had confirmed HR-HPV eradication after 3 to 6 months of AHCC 3g. Similarly, 4 of 9 (44%) patients had confirmed HR-HPV eradication after 7 months of AHCC 1g. Suppression of IFN beta<25 pg/mL was observed in those eradicating the HPV infection. Conclusion: Pre-clinical in vitro and in vivo studies demonstrated durable eradication of HPV infections. Both pilot studies suggested that AHCC supplementation supports the host immune system for successful eradication of HR-HPV infections. A confirmatory phase II randomized, double-blinded, placebo-controlled study is ongoing.